Pembentukan Karakter Peduli Lingkungan Pada Masyarakat Desa Wisata Nusa Kecamatan Lhoknga Kabupaten Aceh Besar - Rusli Yusuf; Ruslan, Ruslan; Rayyan Wahyu Maulana (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
The formation of an environmentally caring character through the village government and the Nusa Tourism Institute as well as Nusa Village community leaders is a general illustration where the development of environmentally caring attitudes and behavior can be started at the village level. The development of attitudes and behavior that cares about the environment nationally can of course start with development at the level of the smallest community unit, namely the village. This research aims to (1) identify the role of the Village Government and the Nusa Tourism Institute in forming an environmentally caring character in Nusa Village, Lhoknga District, Aceh Besar Regency. (2) To determine the role of community leaders in forming environmentally caring character in Nusa Village, Lhoknga District, Aceh Besar Regency (3) To explain the form of cooperation between the Village Government and the Nusa Tourism Institute with community leaders in forming environmentally caring character in Nusa Village, District Lhoknga, Aceh Besar Regency. This research uses a qualitative method with a descriptive research type, the data sources in the research are 6 people consisting of the Village Head, Village Secretary, General Chair of the Nusa Tourism Institute, Head of the Nusa Tourism Institute's Guiding Division, Chair of the village tuha peut, and meunasah imam. Data collection techniques use interviews, observation and documentation. The results of this research show that the role of village government includes establishing and optimizing LPN performance, coordinating and deliberating between institutions, executing correspondence service programs, monitoring, facilitating and assisting cooperative relations between village and non-village institutions. Meanwhile, the LPN's role includes coordination and deliberation, implementation of socialization which includes door to door activities, mutual cooperation, empowerment of PKK women, reward and punishment regulations for providing hygiene facilities to the community, and organizing environmental events. Apart from that, the role of the meunasah imam includes providing socialization on environmental management procedures based on the Koran and hadith. Meanwhile, the village tuha peut has a role as supervisor and advisor so that all activities remain in accordance with customary, cultural, tradition and sharia values. Forms of cooperation between village government, LPN and community leaders include planning, implementation and checks and balances. So that environmental citizenship in Nusa Village, Lhoknga District, Aceh Besar Regency can be created and implemented well.